1-Heptyne semihydrogenation catalized by palladium or rhodium complexes. Influence of: metal atom, ligands and the homo/heterogeneous condition - Quiroga, Monica Esther (2007)
[RhCl(TDA)3], [RhCl(HA)3], [PdCl2(TDA)2] and [PdCl2(HA)2] (TDA = tridecylamine, HA = hexylamine) were synthesized and tested as catalysts in homogeneous and heterogeneous condition for the 1-heptyne semihydrogenation, using γ-alumina as support. The Lindlar catalyst was used as a reference. XPS, FTIR and Atomic Absorption results showed that the active catalytic species in each case is the complex itself. All of the catalytic systems exhibited a better performance than the Lindlar catalyst, with the exception of [PdCl2(HA)2]. The analysis of activity and selectivity values allowed to say that the best system is [RhCl(TDA)3]/Al2O3, an heterogeneous catalyst with an electron-rich transition metal and an electron-donating ligand (TDA) containing a long-chain hydrocarbon substituent. The complex system catalytic behaviour could be explained by means of electronic and geometric effects.